Evaluating District and Sub-Divisional Court Management in West Bengal - Banerjee, Pradip; Banerjee, Pritam (International Journal of Psychosocial Rehabilitation, 2020)
The society in a democratic polity cannot be conceived without a strong and independent judicial system. India, the world’s largest democracy, suffers from more than four crore pending cases across several district and taluka (sub-divisional) courts at par with the National Judicial Data Grid (NJDG), and such a number has been raised by 13 percent only between 2019 and 2020. There are a number of judicial or legal procedural factors that contribute to the backlog that always lies in the limelight. On the other hand, the conflict and contrast between the aspiration and achievement of performance of the courts and judges are hardly measured. It is undeniable that without the development of internal management and governance, the judicial organisation cannot serve up to the expectations of the people. Accordingly, evolution of the Indian court management system as well as a few marginalised arenas of the district and sub-divisional courts’ management and governance have been explored under this study. Furthermore, comprehensiveness of the specific problems spotted under each domain has been empirically verified from the perspective of different stakeholders of the justice delivery system (such as judges, lawyers, academicians, administrators, and litigants) within the state of West Bengal. This study reveals that an effective and efficient judicial administration prevailed in ancient India. Under this research, nearly 9 out of 10 litigants believe that courts are functioning at a less than optimal level, as well as interestingly, every 3 out of 4 judges disclose that they spend more time in judicial work and less in administration. The study finds that some of those problems are glaring for all the stakeholders, while few of these are stakeholder-specific. The statistical analysis also supports that all the stakeholders have commonality in some of the specific problems, like: length of trial of a case is uncertain; workload in court delays timely justice; court lacks policy for time-bound and cost-effective justice; and courts have poor infrastructure.